INDIGENOUS TRADITIONAL KNOWLEDGE AND USAGE OF FOLK BIO-MEDICINES AMONG RONGMEI TRIBE OF TAMENGLONG DISTRICT OF MANIPUR, INDIA - Prakash, N; Ansari, Meraj Alam; Punitha, P; Sharma, P K (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Rongmei tribe (Kooki), are inhabitant of the Charoi Chagotlong village, Tupul, Tamenglong district of Manipur have the traditional knowledge of folk bio-medicine based on diverse plant species for the prevention and cure of certain chronic diseases. The aim of this study was to document and preserve the indigenous knowledge of the Rongmei tribe on folk medicines. Material and methods: The present work was based on methodical field survey conducted between 2010, to 2013. Local people of within 30-70 age groups of both sexes were interviewed and a group discussion (using a structured interview schedule), was held to know about the type of plant parts used in folk bio-medicines, and their mode of use. The interviewers were drawn from a wide array of disciplines (Vendors, Farmers club, NGO’s, scientific societies, etc.), to obtain maximum information in relation to folk bio-medicine. Results: A total of 60 species belonging to 36 different families (ranging from gymnosperm to angiosperm with medicinal benefits), were discussed briefly with significant emphasis on their local name, scientific name, family, parts used; they claimed to cure various ailments from these plants in this mode of folk bio-medicine. The different plant parts used were leaves, fruits, bulbs, bark, roots, seeds, tuber, trunk, flower, shoot, whole plant, rhizome, stem, wood and berries. Based on a life form of the reported plants comprise herbs, shrubs, trees, grasses, bulb, vine, climber, tuber and succulent. Conclusion: Efforts should be made to promote the use of traditional biomedicines within rural communities to preserve the traditional knowledge.